Professionally oriented approach to the law students language teaching - Koleуeva, E.R.; Bobykina, I.A. (Ye.A.Buketov Karaganda State University Publ., 2014)
The article considered the meaning and essence of professionally oriented approach to teaching a foreign language lawyer's specialty. Analyzed occupational characteristics, features of professional thinking and consciousness of a lawyer. Noted that professional foreign language teaching has its own peculiarities, and is based on competence and student-centered approach, in which the student is an active participant in the educational process. The authors pointed out that along with the traditional methods of effective language teaching technologies of e-learning promotes the quality of law students language teaching.
Болашақ заңгер студенттерді шет тіліне кəсіби бағдарланған түрде оқыту
Профессионально ориентированное обучение иностранному языку студентов — будущих юристов
Keywords: foreign language teaching; law students; professionally oriented approach; portrait of professional lawyer; teaching methods